2009
DOI: 10.1055/s-0029-1237710
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Glycemic Index Meals on Recovery and Subsequent Endurance Capacity

Abstract: This study examined the effect of ingesting a high or low glycemic index (GI) meal during a short-term recovery period on endurance running capacity. On two occasions, seven men (age 30.0+/-2.6 yr, body mass 60.7+/-1.4 kg, VO (2max) 62.1+/-2.2 ml.kg (-1).min (-1)) ran at 70% VO (2max) on a level treadmill for 90 min (R1), followed by a 4 h recovery (REC) and a further exhaustive run at the same speed (R2). Twenty minutes after R1, each subject consumed an isoenergetic meal containing either high GI (HGI, GI=77… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 30 publications
2
17
0
Order By: Relevance
“…Much of the variation in the findings can be attributed to differences in the insulin regimen used by participants, e.g., neutral protamine Hagedorn insulin (22), Ultralente with prandial insulin lispro (28), or insulin glargine with insulins aspart or lispro (38)(39)(40). Although it has been recommended to avoid administration of full rapid-acting insulin dose within 2 h of physical activity owing to the risk of overinsulination of the active musculature during exercise (6,26), administration of reduced doses of rapid-acting insulin with ingestion of CHO within this time has been shown to irnprove postexercise glycemia (41).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Much of the variation in the findings can be attributed to differences in the insulin regimen used by participants, e.g., neutral protamine Hagedorn insulin (22), Ultralente with prandial insulin lispro (28), or insulin glargine with insulins aspart or lispro (38)(39)(40). Although it has been recommended to avoid administration of full rapid-acting insulin dose within 2 h of physical activity owing to the risk of overinsulination of the active musculature during exercise (6,26), administration of reduced doses of rapid-acting insulin with ingestion of CHO within this time has been shown to irnprove postexercise glycemia (41).…”
mentioning
confidence: 99%
“…However, although studies have demonstrated the importance of a CHO's GI in influencing exercise capacity in nondiabetic individuals by sueh mechanisms (23), results have been equivocal (41). Furthemiore, no research has addressed the relationship between CHO type and endurance performance in TIDM individuals.…”
mentioning
confidence: 99%
“…In the study that found performance advantages in the high GI group, 18 it was verified that the amount of CHO used was of 1.5 g/kg, being a planned meal with high GI foods, such as potato, tomato sauce, white bread, processed cheese, and watermelon.…”
Section: Performancementioning
confidence: 97%
“…However, only five found significant results. [16][17][18][19][20] Two studies measured time to complete the test 17,19 and the use of low GI-favored performance in these studies (high x low GI: 95.6 ± 6.0 minutes x 92.5 ± 5.2 minutes; 96 ± 7 minutes x 93 ± 8 minutes; 31.08 ± 6.27 minutes x 30.05 ± 4.7 minutes., P < 0.05, respectively). This same advantage can be observed in 2 other studies 16,20 which evaluated time to exhaustion, The low GI group obtained higher glycemia in the first 30 minutes of exercise; however, there was no difference between the two groups after the first 30 minutes of running; RER values were higher during the first 90 minutes of running in the high GI group; FFA and glycerol concentrations were significantly higher in the low GI group during all exercises, accompanied by a higher rate of fat oxidation.…”
Section: Biochemical Parametersmentioning
confidence: 99%
“…Some starches appear suitable when consumed before 40 or in recovery from 43 exercise as a performance improvement has been observed in specific conditions for specific starch-containing foods 45 . Moreover, a low glycaemic index (GI) CHO appears to hold some advantage over a high GI CHO when ingested prior to exercise, 45 and the reverse is thought to occur post-exercise when the recovery period is short, 46 but not long 47 Table 1.Studies investigating the effect of starches on exercise performance.StudyStarch typeIngestion TimingProtocolPerformanceGoodpaster et al 40 Waxy (100% amylopectin), or resistant (100% amylose)30 min before exercise60 min cycling at 75% O 2 max, 30 min TT6.3% improved performance with waxy cornJozsi et al 41 Waxy (100% amylopectin) or resistant (100% amylose)Post-exercise consumption over 12 h60 min cycling at 75% O 2 max, 6 × 1 min at 125% O 2 max, 24 h rest, 30 min TTNo effectRoberts et al 42 Waxy (95% amylopectin), hydrothermally modified30 min before exercise150 min cycling at 70% O 2 max, TTE at 100% O 2 maxNo effectStephens et al 43 Low and high molecular weight modified corn starchesPost-exercise feeding 2 h prior to second boutTTE cycling at 73% O 2 max, 2 h rest, 15 min TT2.3% improved TT performance with high molecular modified starches

Notes: TTE, time to exhaustion; TT, time trial; O 2 max, maximal O 2 consumption.

…”
Section: Supplementation For Sport: Starch and Sagomentioning
confidence: 99%